2001
DOI: 10.1002/1099-0690(200104)2001:8<1569::aid-ejoc1569>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Hypervalent Organo-Iodine(III) Compounds

Abstract: A series of ortho-substituted chiral hypervalent iodine reagents has been synthesized utilizing a zirconium-mediated iodoacylation reaction, which was followed by a stereoselective reduction, methylation, and an oxidation/ligand-exchange sequence. The evaluation of these new compounds as stereoselective electrophilic reagents towards alkenes and ketones is reported. Enantioselectivities as high as 65% have been achieved in the dioxytosylation of styrene and of up to 40% in the oxytosylation of propiophenone. X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 162 publications
(64 citation statements)
references
References 39 publications
2
59
0
3
Order By: Relevance
“…Of these, the 6-ethylsubstituted iodoarene 5 (entry 2) gives the highest enantioselectivity, a fact also observed in the stoichiometric reaction. 1f, 4 We find that the enantioselectivity obtained in this catalytic reaction is the same as that observed in the stoichiometric reaction performed at the same temperature in the same solvent. We have previously reported that methyl ethers give rise to the best selectivity 1f so we did not test any iodoarenes that did not possess the 1-aryl-1-methoxyethane function seen in 4-11.…”
Section: Scheme 1 Enantioselective Oxytosylation Of Ketonesmentioning
confidence: 99%
“…Of these, the 6-ethylsubstituted iodoarene 5 (entry 2) gives the highest enantioselectivity, a fact also observed in the stoichiometric reaction. 1f, 4 We find that the enantioselectivity obtained in this catalytic reaction is the same as that observed in the stoichiometric reaction performed at the same temperature in the same solvent. We have previously reported that methyl ethers give rise to the best selectivity 1f so we did not test any iodoarenes that did not possess the 1-aryl-1-methoxyethane function seen in 4-11.…”
Section: Scheme 1 Enantioselective Oxytosylation Of Ketonesmentioning
confidence: 99%
“…Indeed, computational studies of hypervalent iodine compounds have been performed, but have not addressed the questions posed here. 26,27,52 The trouble with this approach is that without some experimental support (kinetics, transition state energies, etc. ), computational results will not be entirely conclusive.…”
Section: Known Unknownsmentioning
confidence: 99%
“…This led to finding increased selectivities when R 2 = Et, giving the products in 65% ee (bis-oxytosylation of styrene) and 40% ee (α-oxytosylation of propiophenone). 8 The importance of the ortho-substituent R 2 on the reactivity of the iodine(III) center has recently been shown through further computational evidence. 9 The enhanced catalytic activity of iodoarenes such as 4 has been ascribed to the destabilizing effect of this substituent, with these catalysts giving the products in good yields (70-85%) after several hours at a temperature of -30 °C.…”
Section: Stereoselective Reactionsmentioning
confidence: 99%